Revitalisasi Perekonomian Masyarakat melalui Digitalisasi Produk UMKM dan Pembelajaran Financial technology di Desa Bugbug, Karangasem, Bali - Juliati Prihatini; I Made Aldy Wijaya (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2023)
The economic sector is one of the vital sectors of society that has been negatively affected by the outbreak of the Covid-19 Pandemic. In the economic sector, economic digitalization is one solution that can be applied. The form of economic digitalization that can be done to support the National Economic Recovery Program is the digitalization of SME products and the implementation of financial technology. This study aims to know, analyze, and describe efforts to revitalize the community's economy through digitalization of SME products and financial technology learning in Bugbug Village, Karangasem District, Karangasem Regency, Bali Province. The implementation of activities goes through two stages, namely the pre-implementation stage and the implementation stage. In the pre-implementation stage, they succeeded in finding samples of SME actors in Bugbug Village through a field survey process, namely B-Oxy Oxygen Mineral Water and the Es Cendol Cincau Komang Ariawan business. At the implementation stage, the sample of SME owners taken by researchers was given education to be able to understand and understand how product digitization can be done through social media. However, they are still unable to implement the QRIS payment system introduced by the researchers on the grounds that they are still happier with the cash payment system. To overcome these obstacles, it is recommended that village officials together with local governments can form more community programs oriented towards the introduction of digitalization of SME products and the use of QRIS as part of financial technology that shortens the flow of financial transactions.